Role of Wnt signalling in early pregnancy - Nayeem, S.; Arfuso, Frank; Dharmarajan, Arunasalam; Keelan, J. (C S I R O Publishing, 2015)
The integration of a complex network of signalling molecules promotes implantation of the blastocyst and development of the placenta. These processes are crucial for a successful pregnancy and fetal growth and development. The signalling network involves both cell–cell and cell–extracellular matrix communication. The family of secreted glycoprotein ligands, the Wnts, plays a major role in regulating a wide range of biological processes, including embryonic development, cell fate, proliferation, migration, stem cell maintenance, tumour suppression, oncogenesis and tissue homeostasis. Recent studies have provided evidence that Wnt signalling pathways play an important role in reproductive tissues and in early pregnancy events. The focus of this review is to summarise our present knowledge of expression, regulation and function of the Wnt signalling pathways in early pregnancy events of human and other model systems, and its association with pathological conditions. Despite our recent progress, much remains to be learned about Wnt signalling in human reproduction. The advancement of knowledge in this area has applications in the reduction of infertility and the incidence and morbidity of gestational diseases.